2016
DOI: 10.3390/atmos7100130
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Preliminary Breakdown and Return Stroke Processes in High-Intensity Negative Lightning Discharges

Abstract: Abstract:Using an automated data processing algorithm, we examined electric field records of 5498 negative cloud-to-ground flashes reported by the U.S. National Lightning Detection Network (NLDN) within 50 to 500 km of the Lightning Observatory in Gainesville (LOG), Florida. Out of the 5498 flashes, 3496 (64%) had detectable preliminary breakdown (PB) pulse trains. Only 3077 flashes with a single PB pulse train and NLDN-reported first-return-stroke (RS) peak current ≥50 kA were selected for detailed analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 24 publications
8
19
0
Order By: Relevance
“…Observe again that the average speed increases with increasing peak current, increasing streamer speed, and decreasing potential gradient. This result is in agreement with the results presented by Zhu et al [27], in which it was found that negative lightning flashes with faster stepped leaders tend to have higher first return stroke peak currents. However, it is the change in step length that influences the leader speed more than the time of formation.…”
Section: Stepped Leader Speedsupporting
confidence: 94%
See 1 more Smart Citation
“…Observe again that the average speed increases with increasing peak current, increasing streamer speed, and decreasing potential gradient. This result is in agreement with the results presented by Zhu et al [27], in which it was found that negative lightning flashes with faster stepped leaders tend to have higher first return stroke peak currents. However, it is the change in step length that influences the leader speed more than the time of formation.…”
Section: Stepped Leader Speedsupporting
confidence: 94%
“…Unfortunately, almost all the studies do not give the prospective return stroke peak current, and, for this reason, a direct comparison is impossible in the present study. The study also shows that the leader speed increases with increasing peak current and this tendency is also observed in the experimental data of Campos et al [26] and Zhu et al [27].…”
Section: Discussionsupporting
confidence: 82%
“…Yoshida et al 30. reported upward positive leader (UPL) speeds of the order of 10 6  m/s (the corresponding leader current was of the order of kiloamperes) in rocket-triggered lightning, and Zhu et al 31. inferred similarly high speeds for exceptionally fast negative stepped leaders initiating return strokes with peak currents in excess of 100 kA in natural lightning.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our results are also consistent with those of Zhu et al . [] who reported that the PB‐to‐RS interval was found to decrease with increasing RS peak currents for 3077 negative first strokes with peak currents equal to or greater than 50 kA occurring in an area including both land and ocean in and around Florida. In Figure d, the median leader duration for different ranges of NLDN‐estimated peak current ( I P bins) are shown for the five regions considered here.…”
Section: Duration Of Negative Stepped Leadermentioning
confidence: 99%